Assessing the rural cultural significance for heritage tourism development in Perak Tengah District / Siti Norlizaiha Harun and Mohd Roswodi Mat Zin - Siti Norlizaiha, Harun; Mohd Roswodi, Mat Zin (Universiti Teknologi MARA, Perak, 2018)
The cultural heritage resources are widely available in the rural area in the form of a unique culture and art, heritage, traditional knowledge, natural beauty, ecological resources and others, and are representative of the community culture. Heritage interpretation is an educational process that aims to reveal meanings about our culture. Good interpretation enhances our understanding, appreciation, and therefore, provides protection of cultural heritage. This research has two aims; 1) to identify the cultural heritage significance; 2) to designate interpretation plan of the potential cultural heritage for new tourist attraction in the state of Perak. The method of this research involved three steps; inventory of resources, focus group survey and interpretation proposal. Results from focus group indicate the need to customize the interpretation and presentation of rural heritage especially on physical experience in community cultural activities. This study also highlights the most significance cultural resources in Perak Tengah Districts based on ranking. The output of this research is to produce the interpretation guidance for heritage site operators on how visitors can experience our cultural heritage in the rural area.